Exposure assessment of Salmonella related to pork handling and consumption at households in Hung Yen and Nghe An provinces - Ngan Tran Thi; Dang Xuan Sinh; Unger, Fred; Barot, M.; Hung Nguyen-Viet; Pham Van Hung; Grace, Delia; Phuc Pham Duc (2017)
Introduction: Along with poultry and eggs, pork meat represents one of the most signiﬁ cant risks of Salmonellosis. Pork accounts for 56% of the meat consumed daily in Vietnamese households and pork preparation and handling poses a major risk due to possible cross-contamination. The objective of this study is to conduct the exposure assessment by determination of Salmonella prevalence, concentration in market purchased pork and pork handling, and consumption at households in term of food safety in Hung Yen and Nghe An provinces. Methods: A total of 217 pork samples were collected from pork shops in wet markets for Salmonella analysis between April 2014 and February 2015. A cross-sectional survey on pork handling and consumption at households was also conducted using a structured questionnaire in 416 households in these two provinces. Results: Overall Salmonella prevalence in market pork was 44.7% with an average concentration of 9 (<0.3 to >110) MPN/g. Most of consumers purchased pork at the market in the morning around 7:30 am with an average purchase amount of 0.45 (0.1-9.5) kg pork/ time. The methods used for storing raw pork before cooking were at room temperature (54.6%, 228/416) or in a refrigerator (41.8%, 174/416)) with an average duration of 0.6 and 2.4 hours, respectively. The percentages of household using the same knife or cutting board to prepare both raw and cooked pork were 80.5% and 74.5%, respectively. Conclusion: These ﬁ ndings highlight the high level of Salmonella in pork sold at informal retail markets. This study also shows that the behavior and practices of Vietnamese consumers can present a risk of Salmonella cross-contamination in the household that required the training and education programs on food safety practice of consumer.